Syaikhona Kholil Bangkalan Madura Scientific Network: Historical Analysis of Sanad, Teachers, and Students in the Transmission of Islamic Science in the Archipelago - Moch Hizam; M. Yunus Abu Bakar (Universitas Muhammadiyah Enrekang, 2026)
This study comprehensively analyzes the scholarly network (jaringan keilmuan) of Syaikhona Muhammad Kholil bin Abdul Lathif al-Bangkalani (1835–1925), the greatest Islamic scholar of the Malay-Indonesian Archipelago (Nusantara), based in Bangkalan, Madura. Employing intellectual history and descriptive social network analysis, the research traces four main dimensions: (1) his intellectual genealogy through his teachers in Madura, Java, and Haramayn; (2) the model of knowledge transmission at his Bangkalan pesantren including disciplines taught and pedagogical methods; (3) the dispersal of his students who subsequently established major pesantren and Islamic organizations across the Archipelago; and (4) the impact of this scholarly network on the character of Nusantara Islam—moderate, tolerant, and tradition-based (ahlussunnah wal jamaah). Using qualitative-historical library research on manuscripts, colonial archives, and academic literature, the study finds that Syaikhona Kholil constituted the central hub of the Islamic scholarly network in 19th–early 20th century Nusantara, with over 500,000 students who studied under him. The chains of transmission (sanad) of most Indonesian ulama of the era trace back to him, making him the 'common link' in Nusantara Islamic knowledge transmission. This study affirms that his scholarly network was not merely a regional Madura-Java phenomenon, but a trans-archipelago Islamic knowledge system connected to the Haramayn scholarly network.